Surgical treatment of gunshot penetrated wounds of elbow joint - Borzykh, Natalia; Strafun, Oleksandr; Vlasenko, Maksim (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Treatment of patients with gunshot penetrated wounds of elbow joint — is complicate problem. In case of combination of soft tissues and bone structure defeat in this area, the risk of complications increase, it can lead to negative results. Objective: to optimize the basic elements of surgical treatment of patients with gunshot penetrated polistructural wounds of elbow joint in order to get appropriate anatomic and functional result. Methods: we analyzed results of treatment of 31 patients with polistructural wounds of elbow joint. Patients were treated with the system ASES. During the first week after trauma 24 patients were hospitalized (the 1st group), in 1–6 months — 7 patients (the 2nd g roup). Results: in 2 4,4 % have got polistructural wounds of elbow joint, among them 67,7 % — had the III–IV degree. In the 1st group reconstructive surgeries were made in early terms (in average in (21,0 ± 3,2) days). At the same time we made surgeries on the reason of severe intraarticular fractures, damages and soft tissues defects. We have got excellent (3 patients), good (11) and satisfactory (10) results. In the 2nd group infection complications were revealed such as sinus tracts, rough scars because of unvascularised types of grafts application in the elbow region, restriction or absence of joint movements. Reconstructive-plastic surgeries were made in (73,0 ± 6,5) days after trauma. We have got good (1 patient), satisfactory (4) and unsatisfactory (2) results. Conclusions: the key moment in the treatment of patients with polistructural penetrated wounds of elbow joint of the III–IV degree is soft tissues restoration. Expediently is to combine the stages of reconstructive surgeries.